Management of Recurrent Trigeminal Neuralgia Associated with Petroclival Meningioma - Bir, Shyamal C.; Maiti, Tanmoy Kumar; Bollam, Papireddy; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objective Petroclival meningioma (PM) presents with trigeminal neuralgia (TN) in < 5% of cases. Neurosurgeons often face the dilemma of formulating a treatment protocol when TN recurs. In this study, we sought to set up a protocol in patients with PM who had a recurrent TN.Materials and Methods We performed a retrospective review of 57 patients with PM. Of the 57 patients, only 7 patients presented with TN, and six patients experienced recurrent TN. The study population was evaluated clinically and radiographically after treatment.Results Overall improvement of pain control after various treatments was 67%, and tumor control was 100%. The pain-free period was 2 years for the Gamma Knife radiosurgery (GKRS) group and 4 years for the resection group when treated as a primary treatment (p = 0.034). Of the six patients, four patients had Barrow Neurosurgical Institute (BNI) score I (no TN, no medication), and two patients had BNI score III (some pain controlled with medication). The Karnofsky performance scale score was significantly improved after treatment compared with the pretreated status (78 versus 88; p = 0.044).Conclusion Microsurgical resection is superior to GKRS in achieving and maintaining pain-free status in patients with recurrent trigeminal pain associated with PM.
Keywords: petroclival meningioma; recurrent trigeminal neuralgia; management; outcome